Postnatal acquired toxoplasmosis patients in an infectious diseases reference center - Cassius Schnell Palhano Silva; Elizabeth de Souza Neves; Eliezer Israel Benchimol; Danielle Ribeiro de Moraes (Brazilian Journal of Infectious Diseases)
Infection caused by Toxoplasma gondii, toxoplasmosis, is one of the most frequent zoonoses in the world; it normally affects both genders equally. Humans are one of several possible intermediate hosts, and the disease is oligosymptomatic in most cases. Vertical transmission is an important cause of fetal malformation and sequels in newborns. Approximately 10% of postnatal cases present multiple manifestations, ranging from low fever and mild lymphadenopathy to severe encephalitis. In moderate cases, lesions such as retinochoroiditis may emerge during acute infection or even years later. We analyzed 313 cases of toxoplasmosis from 1992 to 2004, including 261 acute cases. Most patients were women (68.1%), and 39% of these were pregnant. Among acute infection cases, 64.8% presented symptomatic disease; the most frequent manifestations were lymphadenomegaly (59.8%), fever (27.2%), headache (10.7%), asthenia (10%), weight loss (8.4%), myalgia (8%), retinochoroiditis (3.4%) and hepatosplenomegaly (1.5%). Although ocular lesions by T. gondii are well documented as a possible consequence of postnatal infection, two patients developed retinochoroiditis only two years after primary infection. This demonstrates the need for toxoplasmosis case surveillance, even long after acute manifestations.